Response of Transport Parameters and Sediment Microbiota to Water Table Fluctuations in Laboratory Columns. Issue 5 (1st July 2015) - Rühle, Franziska A.; von Netzer, Frederick; Lueders, Tillmann; Stumpp, Christine
Abstract : Groundwater table fluctuations create a dynamic interface between the unsaturated and saturated zone with spatially as well as temporally changing water content and water fluxes. Our objective was to investigate the impact of periodic water table fluctuations on transport parameters, geochemical gradients, and bacterial abundance and community structure in groundwater sediments. We conducted tracer experiments in one‐dimensional column systems investigating vertical flow with static or fluctuating water tables, constantly infiltrated with groundwater and model dissolved organic carbon (DOC). Pore water sampling was performed throughout the experiments, and sediment bacteria of both systems were characterized after completion of the experiment. Our results indicate that neither the longitudinal dispersivity nor column geochemistry was affected by the applied water table fluctuations. However, water content and flow velocities varied dynamically over time and depth in the fluctuation zone. Depth‐resolved bacterial community composition was clearly distinct, with additional populations detected especially in the fluctuation zone. These were absent in the static column, while overall bacterial diversity was similar over depth in both columns. We assume that spatial and temporal changes in water content and/or flow velocities were driving these microbial distinctions. This implies that complex feedback mechanisms between local hydrology and sedimentary bacterial communities in porous media exist. These results are important for the understanding of transformation and biodegradation processes at groundwater tables under increased hydraulic forcing.